Strategi Bertahan dan Ukuran Keberhasilan E-Business - Viantika, Dinda Savira; Siregar, Dedy Rahman; Nurbaiti, Nurbaiti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
The rapid development of technology today requires a business strategy in sales as the spearhead of a business that is increasingly leading to the mastery and use of technology. In order to survive the Covid-19 pandemic, SMEs making kitchen knives Hadipolo Kudus Regency as partners must be able to take advantage of technological developments by doing online business (e-business). Today, many business practitioners and academics believe that a new economic paradigm has been born. some call it e-economy, while others prefer to use terms such as internet economy, digital economy, new economy, and so on. The development of e-business and the use of internet technology significantly improve the way companies interact with customers and suppliers. Well-developed and used e-business strategies and tools have a positive impact on business success.